Criminological Perspectives on Criminal Law Enforcement in Human Trafficking Cases: A Literature Review - Lukmantara, Riekhan Habib; Suwito, Suwito; Darmawan, Didit (Bulletin of Science, Technology and Society, 2022)
This study aims to analyze the criminological aspects underlying criminal law enforcement efforts in dealing with trafficking in persons (TPPO) in Indonesia. This study highlights the role of the criminological approach in understanding the background of perpetrators, the dynamics of crime, as well as the implications for victim protection. This study discusses strategies that can be applied to strengthen regulations and policies in preventing and eradicating TPPO. This study uses a normative juridical method with a literature study approach. The analysis shows that although regulations such as Law No. 21/2007 on the Eradication of Human Trafficking have provided a strong legal foundation, implementation in the field still faces various obstacles, such as weak law enforcement, lack of victim protection, and the complexity of transnational crime networks. The critical criminology approach is relevant in providing a broader perspective on the root causes of TPPO, including the social, economic and political factors behind this crime. Recommendations put forward in this study include strengthening inter-agency synergies, improving training for law enforcement officers, and developing criminology-based policies to reduce the risk of trafficking in the future.